P058 IL-36 signaling in Crohn's disease – characterization of a patient with an IL36RA mutation. (21st January 2022) - Hecker, J; Letizia, M; Loescher, B S; Franke, A; Weidinger, C; Siegmund, B
Abstract: Background: The interleukin 36 (IL-36) family consists of three agonists (IL-36α, IL-36β, IL-36γ), which activate the NF-κB pathway and lead to the production of pro-inflammatory cytokines and the natural antagonist (IL-36RA), which inhibits IL-36 signaling. While it is known that IL-36 signaling is important in the skin, it has been only recently reported that IL-36 might play an important role in maintaining gut homeostasis and in the development of fibrosis (Scheibe et al., 2019). However, it is not clear how IL-36 signaling contributes to the development of intestinal inflammation and which cell types are involved in this process. To shed more light on the role of IL-36 in intestinal inflammation, we took the opportunity to perform an in-depth characterization of a Crohn's disease patient with a mutation in IL36RA and identify cell subsets responding to IL-36 stimulation. Methods: By whole exome-sequencing of EDTA blood we identified in a Crohn's disease patient a heterozygous mutation in IL36RA (p.Ser113Leu), which we confirmed by Sanger sequencing. By ELISA, we quantified IL-36RA serum levels in comparison to other Crohn's disease (CD) patients and healthy donors (HD). Finally, we stimulated peripheral blood mononuclear cells (PBMCs) of the IL-36RA patient, CD patients, and HDs with ionomycin/PMA, LPS or IL-36α and performed deep immune profiling by mass cytometry with 35 markers. Results: Our IL36RA mutation carrying patient presented with a severe course of Crohn's disease and consecutive of fibrosis, which was resistant to all commonly used treatment options. As an individual treatment, autologous stem cell transplantation was performed, but did not lead to long-term improvement in symptoms. By ELISA, we found strongly elevated IL-36RA levels in the serum of our patient compared to CDs and HDs. Mass cytometry analysis revealed that the IL36RA mutation does not lead to major shifts in the immune cell composition of the blood, as the frequencies of B, T, NK, and myeloid cells in PBMCs of our patient were comparable to those in HDs and CDs. Furthermore, our data revealed that IL-36α stimulation mainly induced TNFα and IL-6 expression in myeloid cells as well as IFNγ expression in NK cells but did not affect T and B cells. Conclusion: Our data is the first description of a Crohn's disease patient with an IL36RA mutation and indicate that defects in IL-36 signaling should be considered as a possible cause for therapy-refractory and fibrotic Crohn's disease. Furthermore, we identified NK cells and myeloid cells as main responders to IL-36α stimulation. As next step, we plan to use recombinant produced, mutant IL-36RA in in-vitro assays with immune cells and fibroblasts to study the effect of the mutation on the IL-36RA function in more depth.